PROCEDURAL DOCUMENT: STRUCTURING FEATURES - Umida Pulatova (American Journals Publishing, 2023)
This article discusses the role of speech culture in the future professional activities of a lawyer. In particular, it pays attention to the issues of structuring the text of legal content: resolutions and protocols, reveals linguistic features in connection with parts of documents.
Keywords: culture of speech, written speech, procedural documents, structure of the decision, structure of the protocol, decision, protocol.